Dual closed-loops current controller for a 4-leg shunt APF based on repetitive control. Issue 3 (4th March 2019) - Jian, Le; Xingrui, Li; Jiangfeng, Zhu; Hao, Zhang; Li, Fucheng
ABSTRACT: Current repetitive control strategy for a 4-leg APF is usually of a poor speed in responding to the drastic changes in load harmonic profile. In this paper, a dual closed-loop current controller composed of a repetitive control-based outer loop and a PI-based inner loop is proposed to improve the performance of a 4-leg APF, with a focus on response speed and harmonic current compensation gain. The principle of the dual loop controller is explained in detail, and the stability of the system is analysed thoroughly. To further decrease the inherent time delay associated with the PWM strategy, a zero-sequence-voltage-based PWM strategy is proposed to solve the complexity in the implementation of 3D-SVPWM methods. By formulating the relationship between the duty ratio of the neutral leg control pulse and the zero-sequence-component of the reference voltages, the duty ratios of the other three legs can be calculated conveniently. The simulation and lab experiment results are provided to verify the correctness and effectiveness of the proposed dual closed-loop current controller and the zero-sequence-voltage-based PWM strategy.